GSTP1 and ABCB1 Polymorphisms Predicting Toxicities and Clinical Management on Carboplatin and Paclitaxel‐Based Chemotherapy in Ovarian Cancer - Amanda Canato Ferracini; Leisa Lopes-Aguiar; Gustavo Jacob Lourenço; Adriana Yoshida; Carmen Silva Passos Lima; Luis Otávio Sarian; Sophie Derchain; Deanna L. Kroetz; Priscila Gava Mazzola (Wiley, 2021)
Variation in drug disposition genes might contribute to susceptibility to toxicities and interindividual differences in clinical management on chemotherapy for epithelial ovarian cancer (EOC). This study was designed to explore the association of GST and ABCB1 genetic variation with hematologic and neurologic toxicity, changes in chemotherapy, and disease prognosis in Brazilian women with EOC. A total of 112 women with a confirmed histological diagnosis of EOC treated with carboplatin/paclitaxel were enrolled (2014-2019). The samples were analyzed by multiplex polymerase chain reaction (PCR) for the deletion of GSTM1 and GSTT1 genes. GSTP1 (c.313A>G/rs1695) and ABCB1 (c.1236C>T/rs1128503; c.3435C>T/rs1045642; c.2677G>T>A/rs2032582) single nucleotide polymorphisms (SNPs) were detected by real‐time PCR. Subjects with the GSTP1 c.313A>G had reduced risk of anemia (odds ratio (OR): 0.17, 95% confidence interval (CI): 0.04-0.69, P = 0.01, dominant model) and for thrombocytopenia (OR: 0.27, 95% CI: 0.12-0.64, P < 0.01; OR 0.18, 95% CI 0.03-0.85, P = 0.03, either dominant or recessive model), respectively. The GSTP1 c.313A>G AG genotype was associated with a lower risk of dose delay (OR: 0.35, 95% CI: 0.13-0.90, P = 0.03). The ABCB1 c.1236C>T was associated with increased risk of thrombocytopenia (OR: 0.15, 95% CI: 0.03-0.82, P = 0.03), whereas ABCB1 c.3435C>T had increased risk of grade 2 and 3 neurotoxicity (OR: 3.61, 95% CI: 1.08-121.01, P = 0.03) in recessive model (CC + CT vs. TT). This study suggests that GSTP1 c.313A>G, ABCB1 c.1236C>T, and c.3435C>T SNP detection is a potential predictor of hematological toxicity and neurotoxicity and could help predict the clinical management of women with EOC.